Recent Progress in Nuclear Lattice Simulations - Dean Lee (Frontiers in Physics, 2020)
We review several recent results on lattice simulations by the Nuclear Lattice Effective Field Theory Collaboration. In the first part we discuss the implementation of nuclear forces on the lattice using chiral effective field theory. The new development we highlight is the use of non-local lattice operators to achieve a simpler spin channel decomposition, in contrast with previous studies that considered only local interactions. In the second part, we present evidence that nuclear physics is close to a quantum phase transition. This development is also linked to the study of the differences between local and non-local interactions. In the final part we further explore the link between the nuclear forces and nuclear structure. We consider the simplest possible nuclear interaction which can accurately reproduce the ground state energies of neutron matter, light nuclei, and medium-mass nuclei. We discuss what these recent developments say about the emergence of nuclear structure from nuclear forces and the road ahead for nuclear lattice simulations.